Modificación superficial de fieltro de grafito con nanopartículas de magnetita Fe3O4 para su uso en un sistema electro-Fenton - Calderón Zavaleta, Sandy Luz (2019)
In this work, an electro-Fenton system was manufactured for the degradation of aromatic-type contaminants in aqueous pollutants and the simultaneous generation of electrical energy. The system consisted in two chambers (anode and cathode) separated by a Nafion membrane. The electrical energy was generated by anodic oxidation of glucose catalyzed by gold. The cathode was made of graphite felt modified on its surface with magnetite nanoparticles (Fe3O4NPs/GFoxi). The magnetite nanoparticles were impregnated on graphite felt by means of a layer-by-layer self-assembled method that uses polydiallyldimethylammonium chloride (PDDA) as a polyelectrolyte. In the anodic chamber, a graphite felt surface modified with gold nanoparticles (AuNPs/GF) was used. The nanoparticles were deposited on the surface of this electrode by electrochemical deposition. The electro-Fenton system generated an average output power of 550 mW m-2, which served as a power supply for carry out pollutant degradation process. This system led to the degradation of 0.35 mmol L-1 of hydrogen potassium phthalate (model pollutant) attaining 73.7% of COD decay during 23 h of treatment at pH 3.